Download presentation
Presentation is loading. Please wait.
1
INVERSE FUNCTIONS
2
Steps for Finding the Inverse of a Function
y = f -1(x) Solve for y Trade x and y places Replace f(x) with y
3
Letβs check this by doing
Find the inverse of y = f -1(x) Solve for y Trade x and y places Replace f(x) with y
4
Find the inverse of a function :
Example 1: f(x) = 6x - 12 Step 1: Change f(x) to y: y = 6x - 12 Step 2: Switch x and y: x = 6y - 12 Step 3: Solve for y: x +12 = 6y π+ππ π =y π= π π +2 Step 4: Change y to π βπ π : π βπ (x) = π π +2
5
Given the function: f(x) = 3x2 + 2 find the inverse:
Example 2: Given the function: f(x) = 3x find the inverse: Step 1: Change f(x) to y: y = 3x2 + 2 Step 2: Switch x and y: x = 3y2 + 2 Step 3: Solve for y: Step 4: Change y to π βπ π : π β1 (π₯)= π₯β2 3
6
Ex: Find an inverse of y = -3x+6.
Steps: -switch x & y -solve for y y = -3x+6 x = -3y+6 x-6 = -3y
7
Finding the Inverse Try
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.